2020
DOI: 10.1080/1057610x.2020.1780021
|View full text |Cite
|
Sign up to set email alerts
|

How Do Leadership Decapitation and Targeting Error Affect Suicide Bombings? The Case of Al-Shabaab

Abstract: Targeted killing is a cornerstone of counter-terrorism strategy, and tactical mistakes made by militant groups are endemic in terrorism. Yet, how do they affect a militant group's suicide bomber deployment? Since joining Al-Qaeda, Al-Shabaab has carried out various types of suicide attacks on different targets. Using a uniquely constructed dataset, I introduce two typologies of suicide bomber detonation profilessingle and multipleand explore the strategic purposes these have served for the group during multiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…62 As one study on the impact of attempted leadership decapitation on Al-Shabaab concluded, 'there is evidence that leadership decapitation significantly increased the potency of Al-Shabaab' after Ahmed Godane was also assassinated via the US drone strike in September 2014. 63 In October 2022, the US carried out yet another airstrike in Somalia, killing senior Al-Shabaab leader and co-founder of the group, Abdullahi Yare. 64 Not only did this killing fail to facilitate the decline of Al-Shabaab, but instead the group redoubled the fervour of attacks, carrying out some of the most intensive and deadliest of the previous decade.…”
Section: The Us Wages Physical and Ideological Warfare On Somaliamentioning
confidence: 99%
“…62 As one study on the impact of attempted leadership decapitation on Al-Shabaab concluded, 'there is evidence that leadership decapitation significantly increased the potency of Al-Shabaab' after Ahmed Godane was also assassinated via the US drone strike in September 2014. 63 In October 2022, the US carried out yet another airstrike in Somalia, killing senior Al-Shabaab leader and co-founder of the group, Abdullahi Yare. 64 Not only did this killing fail to facilitate the decline of Al-Shabaab, but instead the group redoubled the fervour of attacks, carrying out some of the most intensive and deadliest of the previous decade.…”
Section: The Us Wages Physical and Ideological Warfare On Somaliamentioning
confidence: 99%
“…The use of leadership decapitation as a counterterrorism or counterinsurgency tactic has been studied extensively by academics (Jordan 2009; Jordan 2014; Jordan 2019; Johnston 2012; Price 2012; Price 2019; Shire 2020; Tominaga 2018). In general, the removal of key leaders of a militant organization is expected to degrade their pool of top commanders and strategists, which then would undermine the planning and execution of violent operations.…”
Section: Focusing On “Leaders” In Decapitation Effortsmentioning
confidence: 99%
“…For example, Abrahms and Meirau (2017; 832) show that targeting leaders can create leadership deficits, which can “empower lower level members of the organization with inferior civilian restraint,” resulting in reprisals against civilians. Shire shows in his study of al-Shabaab that targeted killings led to a “rapid proliferation of unsophisticated single suicide attacks against civilian and military targets to maintain the perception of the group’s potency,” (Shire 2020). Our purpose is not to adjudicate between the competing perspectives on the strategic utility of leadership decapitation, but rather to suggest that the focus on nuanced outcomes has ignored significant nuance in the inputs as they apply to leadership decapitation efforts.…”
Section: Focusing On “Leaders” In Decapitation Effortsmentioning
confidence: 99%
See 1 more Smart Citation